Water Soluble Molecular Capsules via Multiple Ionic Interactions - Zadmard, Reza; Entezari, Hajar; Ataeian, Parinaz; Mirza-Aghayan, Maryam (Letters in Organic Chemistry, 2013)
In this paper we introduced the formation of a novel type of capsules resulting from the self-association between oppositely charged complementary building blocks in H2O. The assembly is based on the interaction between tetraphosphonatcalix[4]arenes 1 and tetraammonium calix[4]arene 2 and 3. Evidence for the formation of the expected 1:1 assemblies is provided by ESI-MS. Isothermal titration calorimetry (ITC) was carried out to measure the enthalpy and entropy of complex formation for capsule 1+3, with association constants in the range of 106 M-1.
Keywords: Calix[4]arene